Job Security and Faculty Commitment within Higher Education Institutions - Ghimire, Binod; Dahal, Rewan Kumar; Karki, Dipendra (The International Research Journal of Management Science, 2023)
Purpose: The main objective of this study is to examine the relationship between faculty job security and organizational commitment in Nepalese higher education, focusing on qualitative and quantitative job security parameters. Methodology: A cross-sectional methodology was used to examine perceived job security and its impact on academic professionals in the Kathmandu Valley. The study involved developing and distributing a self-administered questionnaire to 210 academics associated with Tribhuvan University from different occupational specialties and pay tiers. Descriptive and causal-comparative research designs were employed in the study. Findings: The study found significant associations between job security and organizational commitment (OC). From the results obtained in regression analysis, the value of adjusted R square was 0.584, signifying that 58.4 % of the variation in organizational commitment was due to qualitative and quantitative aspects of job security. The study's results provide empirical evidence supporting the positive impact of qualitative and quantitative employment security factors on OC. Keeping all other independent measures constant, an increase of one unit in qualitative forces would increase OC by 0.522 units (β = 0.468, p < 0.01), followed by an increase of 0.333 units in OC due to quantitative factors (β = 0.286, p < 0.01). Implications: Commitment was significantly impacted by both the quantitative and qualitative dimensions of job security, suggesting that improving job security measures could lead to higher levels of commitment. These results illustrate the importance of job security in supporting loyalty and productivity in Nepalese academic institutions, emphasizing the necessity for proactive measures to improve job security to increase faculty members' organizational commitment. Originality/Value: This study examines how quantitative and qualitative job security affects organizational commitment in Nepalese academic institutions, providing novel insights. It emphasizes the importance of job security in faculty commitment, emphasizing the necessity for focused interventions to improve qualitative and quantitative aspects of job security.